2024
DOI: 10.1038/s41598-024-52560-z
|View full text |Cite
|
Sign up to set email alerts
|

Introducing graphene quantum dots in decomposable wheat starch-gelatin based nano-biofilms

Marzieh Bakeshlouy Afshar,
Ahmad Poursattar Marjani,
Peyman Gozali Balkanloo

Abstract: This research aims to discover a viable substitute for the common harmful plastic packaging utilized in food products. Citric acid was employed as an accessible and risk-free precursor in synthesizing graphene quantum dots (GQDs). Using the efficient carbonization technique, GQDs were obtained and subsequently transferred to nano-biofilms in varying percentages relative to natural polymers. FT-IR, XRD, FE-SEM, EDX, and AFM analyses were conducted to examine the formation of the nano-biofilms. GQDs demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Carbon-based QDs CDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Paydar et al, 2022), active packaging (Khoshkalampour, Ghorbani et al, 2023), intelligent packaging (Liu et al, 2022), nanocarriers (Shu et al, 2017) GQDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Orachorn & Bunkoed, 2021), active packaging (Bakeshlouy Afshar et al, 2024), nanocarriers (Ghanbari et al, 2021) Cadmium-based QDs CdS QDs Photoelectric properties, antibacterial properties Detection of food analytes (He et al, 2022), active packaging (Grzebieniarz et al, 2021) CdSe QDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Li, Wen et al, 2022), nanocarriers (Yang et al, 2017) CdTe QDs Photoelectric properties, antibacterial properties Detection of food analytes (Liang et al, 2022), intelligent packaging (Fu, Wu et al, 2020) Zinc QDs ZnO QDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Sahoo et al, 2018), active packaging (Schmitz et al, 2020), nanocarriers (Flora et al, 2023) ZnS QDs Photoelectric properties, antibacterial properties Detection of food analytes (Sajwan et al, 2021), active packaging (Shojaeiarani et al, 2022) ZnSe QDs Photoelectric properties, antibacterial properties Detection of food analytes (Jayalakshmi et al, 2024) Silicon QDs SiQDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Na et al, 2019), intelligent packaging (Sun et al, 2023) synthesized ionic liquid-organophilic CDs (IL-OCDs) through a hydrothermal method using imidazolium ILs as precursors and regulators to change the properties of the CDs (Figure 4a). Results demonstrated that IL-OCDs, as nanocarriers and delivery systems, showed a loading ratio of up to 69.2% for curcumin.…”
Section: Food Applications and Representative Referencesmentioning
confidence: 99%
“…Carbon-based QDs CDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Paydar et al, 2022), active packaging (Khoshkalampour, Ghorbani et al, 2023), intelligent packaging (Liu et al, 2022), nanocarriers (Shu et al, 2017) GQDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Orachorn & Bunkoed, 2021), active packaging (Bakeshlouy Afshar et al, 2024), nanocarriers (Ghanbari et al, 2021) Cadmium-based QDs CdS QDs Photoelectric properties, antibacterial properties Detection of food analytes (He et al, 2022), active packaging (Grzebieniarz et al, 2021) CdSe QDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Li, Wen et al, 2022), nanocarriers (Yang et al, 2017) CdTe QDs Photoelectric properties, antibacterial properties Detection of food analytes (Liang et al, 2022), intelligent packaging (Fu, Wu et al, 2020) Zinc QDs ZnO QDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Sahoo et al, 2018), active packaging (Schmitz et al, 2020), nanocarriers (Flora et al, 2023) ZnS QDs Photoelectric properties, antibacterial properties Detection of food analytes (Sajwan et al, 2021), active packaging (Shojaeiarani et al, 2022) ZnSe QDs Photoelectric properties, antibacterial properties Detection of food analytes (Jayalakshmi et al, 2024) Silicon QDs SiQDs Photoelectric properties, antibacterial properties, drug loading Detection of food analytes (Na et al, 2019), intelligent packaging (Sun et al, 2023) synthesized ionic liquid-organophilic CDs (IL-OCDs) through a hydrothermal method using imidazolium ILs as precursors and regulators to change the properties of the CDs (Figure 4a). Results demonstrated that IL-OCDs, as nanocarriers and delivery systems, showed a loading ratio of up to 69.2% for curcumin.…”
Section: Food Applications and Representative Referencesmentioning
confidence: 99%
“…This two-dimensional structure restricts electronic transport in all three spatial dimensions. GQDs possess small dimensions, with a diameter of less than 20 nm (< 20), allowing them to trap excitons effectively 42 .…”
Section: Introductionmentioning
confidence: 99%